1995
DOI: 10.1007/bf01416039
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the shock structures in a regular detonation

Abstract: Abstract. Time-dependent two-dimensional numerical simulations have been used to investigate the detailed shock structures and patterns of energy release in the regions of the triple points and transverse waves in a planar detonation. As the system of shock triple points evolves between collisions, they trace a well shaped cellular pattern characteristic of detonations in argon-diluted, low-pressure mixtures of hydrogen and oxygen. In the region of the triple points, the shock structure evolves continuously fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 10 publications
4
14
1
Order By: Relevance
“…An increase in track angle through the second half of the cell is evident in soot foil tracks of some detonations, particularly those with orthogonal structure [41]. As the transverse wave strength increases with increasing track angle, this is consistent with the evolution of the transverse wave structure observed by some authors [7,49].…”
Section: Triple Point Analysissupporting
confidence: 86%
“…An increase in track angle through the second half of the cell is evident in soot foil tracks of some detonations, particularly those with orthogonal structure [41]. As the transverse wave strength increases with increasing track angle, this is consistent with the evolution of the transverse wave structure observed by some authors [7,49].…”
Section: Triple Point Analysissupporting
confidence: 86%
“…According to the qualitative picture provided by Strehlow and Crooker (1974), just after the triple point collision, the structure appears to be a weak type and evolves to become a strong type. The numerical results of Lefebvre and Oran (1995) and Oran et al (1998) have also suggested that the structure begins as a weak type and changes to the strong type gradually. However, as pointed out by Fickett and Davis (1979), the event taking place through the process and just after the triple point collision for the experiments is still unclear since details are hardly resolved due to the very short space scale and timescale of both the reaction and flow.…”
Section: Comparison With Experiments and Previous Calculationsmentioning
confidence: 92%
“…However, as pointed out by Fickett and Davis (1979), the event taking place through the process and just after the triple point collision for the experiments is still unclear since details are hardly resolved due to the very short space scale and timescale of both the reaction and flow. Lefebvre and Oran's (1995) analysis is based on a coarse grid and may also encounter similar difficulties as in the experiments. Therefore, it is reckoned that only with numerical results with sufficiently high time and spatial resolutions is it possible to verify the fine process of the whole triple collision, deemed not possible with the current state-ofthe-art experiment.…”
Section: Comparison With Experiments and Previous Calculationsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] Shock configurations of detonation, distribution of energy release, and maximum pressure contours have been investigated by numerical simulations. [12][13][14][15][16][17] A main feature of gaseous detonation is the Ó 2005 The Japan Society for Aeronautical and Space Sciences complex interaction of incident shocks, Mach stems, and transverse waves. Triple points are formed at the intersection of the transverse wave with the Mach stem and the incident shock, and diamond-shaped patterns called cellular structures are left on smoked foils.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, marginal detonation denotes for the detonation in a system near the detonation limit, and would fail if the pressure were a little lower or the tube depth a little smaller. Frontal structure has been examined and three types of interaction geometries clarified 13) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%